2011
DOI: 10.1093/ecam/nep077
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality Role on the Phenolics from Cultivated Baccharis dracunculifolia

Abstract: Baccharis dracunculifolia is the source of Brazilian green propolis (BGP). Considering the broad spectrum of biological activities attributed to green proplis, B. dracunculifolia has a great potential for the development of new cosmetic and pharmaceutical products. In this work, the cultivation of 10 different populations of native B. dracunculifolia had been undertaken aiming to determine the role of seasonality on its phenolic compounds. For this purpose, fruits of this plant were collected from populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 36 publications
4
19
1
3
Order By: Relevance
“…Comparing SFE and SLE in terms of antioxidant activity, it can be observed that both presented 280 similar EC 50 values, thus corroborating the fact that the antioxidant activity is not strictly related to the flavonoids content. For instance, the best DPPH antioxidant activity (run 11, 7.581 µg/mL) was neither related with the highest yield nor with the highest total flavonoid content; thus, the antioxidant activity can be due to the presence of several compounds other than flavonoids, belonging or not to the polyphenolic group [51,52].…”
Section: Box-behnken Optimization Of Sfesupporting
confidence: 53%
See 2 more Smart Citations
“…Comparing SFE and SLE in terms of antioxidant activity, it can be observed that both presented 280 similar EC 50 values, thus corroborating the fact that the antioxidant activity is not strictly related to the flavonoids content. For instance, the best DPPH antioxidant activity (run 11, 7.581 µg/mL) was neither related with the highest yield nor with the highest total flavonoid content; thus, the antioxidant activity can be due to the presence of several compounds other than flavonoids, belonging or not to the polyphenolic group [51,52].…”
Section: Box-behnken Optimization Of Sfesupporting
confidence: 53%
“…Also, the total flavonoids of the C. langsdorffii extract obtained by an optimized SLE condition presented 10.2± 0.25 mg/g and quercitrin of 7.70± 0.02 mg/g, both values lower than the SLE values observed in this study [49]. These results may vary because of the plant variability in its secondary compounds" 255 metabolism is influenced by solar irradiation and/or the amount of raining in the season [50].…”
Section: Solid-liquid Extraction (Sle)contrasting
confidence: 53%
See 1 more Smart Citation
“…Aliados aos resultados destes diferentes ensaios, Sousa (2009a) demonstrou que o cultivo desta planta é bastante viável, no que diz respeito à obtenção de extrato bruto e óleo essencial em escala industrial, sendo que a mesma se apresenta pronta para colheita após o 12º mês de cultivo.…”
Section: Enxaguatórios Bucaisunclassified
“…A utilização de B. dracunculifolia pelas indústrias é possível, pois pesquisas demonstraram que o cultivo desta planta e a sua produção em larga escala para fins comerciais são economicamente viáveis (DE SOUSA et al, 2009B) Com relação ao metabolismo secundário, as espécies do gênero Baccharis são caracterizadas pela presença de diterpenos dos tipos clerodano e labdano, inclusive lactonas diterpênicas, além de suas substâncias aromáticas, como flavonóides e derivados do ácido cumárico (BOHLMANN; ZDERO, 1990). Contudo, é sabido que a produção destes metabólitos pela planta é sensível a diversos fatores como variações climáticas, fatores ambientais e, especialmente, interações com insetos e predadores (BAUER, TITTLEL, 1996;HOGEDAL, MOLGAARD, 2000).…”
Section: _______________________________ ____________________________unclassified